2021
DOI: 10.1002/aenm.202100479
|View full text |Cite
|
Sign up to set email alerts
|

Direct Observation of Reductive Coupling Mechanism between Oxygen and Iron/Nickel in Cobalt‐Free Li‐Rich Cathode Material: An in Operando X‐Ray Absorption Spectroscopy Study

Abstract: Development of positive electrode (cathode) materials for Li-ion batteries, possessing high capacity is necessary to meet current energy requirements and hence to facilitate their commercial applications. The layered Li-rich materials with a general composition xLi 2 MnO 3 •(1−x) LiMO 2 (M = Mn, Co, Ni, Fe) are attractive candidates as high-capacity cathode materials as they can deliver long term reversible capacities close to 200 mAh g −1 when cycled within the voltage range 2.0-4.8 V. [1][2][3][4][5][6] In t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
19
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(19 citation statements)
references
References 62 publications
0
19
0
Order By: Relevance
“…Studies have demonstrated that lattice oxygen oxidation can cause charge transfer from oxygen to TM, accompanied by lattice oxygen escape. [ 45 ] The reduction of Mn reduces the density of electronic holes in O2p‐Mn3d, thus weakens the O K‐edge pre‐edge peaks. While due to the inhibition of lattice oxygen redox, the intensity of pre‐edge peaks for charged LMNPO‐V O are almost the same with those for pristine LMNPO‐V O .…”
Section: Resultsmentioning
confidence: 99%
“…Studies have demonstrated that lattice oxygen oxidation can cause charge transfer from oxygen to TM, accompanied by lattice oxygen escape. [ 45 ] The reduction of Mn reduces the density of electronic holes in O2p‐Mn3d, thus weakens the O K‐edge pre‐edge peaks. While due to the inhibition of lattice oxygen redox, the intensity of pre‐edge peaks for charged LMNPO‐V O are almost the same with those for pristine LMNPO‐V O .…”
Section: Resultsmentioning
confidence: 99%
“…When further charging to 4.8 from 4.36 V, it is noted that the "white line" absorption peak remains constant, whereas the Ni K-edge absorption shifts slightly to lower energy, similar to the trend observed in ex situ XAS results in several previous works. [46][47][48] This phenomenon is related to the reduction of a small fraction of Ni 4+ , which is most likely caused by reduced coupling of Ni with oxygen, accompanied by oxidization of oxygen species in the vicinity. [48,49] In contrast, the absorption edge of n-LMNO does not coincide with the pristine state when discharged to 2.0 V (Figure S11, Supporting Information), whereas they overlap exactly in d-LMNO (Figure 4b).…”
Section: Local Atomic Structure Analysismentioning
confidence: 99%
“…To improve the structural stability of Li 2 MnO 3 , the LMR analogues were proposed. [71][72][73][74][75] However, the origin of the high charge capacity and the reason for the oxygen redox are still unclear. Because of the intrinsic complexity of LMR in composition and structure, Tarascon et al 43 4).…”
Section: Other Techniquesmentioning
confidence: 99%